Franchising - ett lyckat koncept för Östgöta Brandstodsbolag? - Klasson, Christian (2008)
Östgöta Brandstodsbolag started its insurance business in 1841 and is today a part of Länsförsäkringsgruppen, which consists of 24 independent and locally anchored county insurance companies. The local concept is a condition for the county insurance (länsförsäkring) idea, which means that the 24 county insurance companies cooperate freely. Länsförsäkringar is the market leader within property and liability insurances in Sweden and has a market share of 30.5%. The largest, and most well known, insurance companies in Sweden, apart from Länsförsäkringar, are If, Trygg-Hansa and Folksam.